'Role of the modulating factors on the self-perceived OHRQoL of fully dentate subjects and wearers of screw-retained and cement-retained implant-supported FPDs: A cross-sectional study'. (February 2022) - Castillo-Oyagüe, Raquel; Río-Highsmith, Jaime Del; Preciado-Uribe, Arelis; Lynch, Christopher D.; García-Minguillán, Gonzalo
Abstract: Objectives: This research aimed to compare the oral health-related quality of life (OHRQoL) between fully dentate subjects and edentulous patients wearing implant-supported fixed partial dentures (i-FPDs). The clinical conditions of both types of restorations were evaluated. Methods: Participants were assigned to: Group-1 (SR, n = 50): screw-retained i-FPD wearers; Group-2 (CR, n = 50): cement-retained i-FPD wearers; and Group-3 (ND, n = 50): dentate subjects with a healthy natural dentition (controls). Patients answered the OHIP-14sp and QoLIP-10 questionnaires. Data related to sociodemographics, prosthesis features, peri‑implant status, complications, and subjective evaluations, were compiled. Potential modulators of the OHRQoL and the i-FPDs' clinical conditions were assessed using non-parametric tests ( α = 0.05). Results: ND individuals were the least satisfied (OHIP-14sp; p < 0.001). Both prosthodontic groups reported similar levels of wellbeing, excluding the speaking difficulties, which were lower for SR wearers as shown by both scales ( p = 0.001). The most discontented patients (OHIP-14sp) were: women ( p = 0.022), under 65 years ( p = 0.03), without partner ( p < 0.001) and having a crown ( p = 0.033). The level of education/schooling also affected the OHIP-14sp scores ( p < 0.001). Implant mobility and peri‑implantitis were more frequent among CR wearers ( p -values= 0.008 and 0.05, respectively). Conclusions: The OHRQoL of both prosthodontic groups was comparably higher than that of the dentate subjects, who were the most nonconformist. The self-perceived satisfaction was mainly modulated by sociodemographic factors. Clinical significance: Overall, the retention system did not impact the OHRQoL, prosthetic problems, and subjective evaluations of i-FPD wearers. However, the cementation may increase the risk of peri‑implant diseases.